Dinâmica geoambiental e repercussões sobre os recursos hídricos do município de Nossa Senhora das Dores/Sergipe : 1970 a 2018 - Leite, Lucas Silva (2020)
The understanding of the dynamics of natural systems and the delimitation of landscape units makes it possible to identify the degree of susceptibility of environments to human actions. The municipality of Nossa Senhora das Dores has 74.2% of its land drained by the hydrographic network of the Sergipe River basin and 25.8% of the Japaratuba River. Its territory presents differences in the physical-biotic components, in the spatial distribution of the population and in the types of land use. The demand for water is growing, both due to the increase in the population, as well as agricultural activities. Thus, this research aims to analyze the dynamics of the geoenvironmental system and the repercussions on the water resources of Nossa Senhora das Dores, in a time frame from 1970 to 2018. The studies were developed according to the systemic conception, guided by the assumptions of the theoretical and methodological model of the geosystem (BERTRAND, 1968), which allows an integrated analysis of the dynamics of the environmental system of the landscape. The methodological procedures included: bibliographic research, survey of the documentary and cartographic collection; field work; processing of satellite images and aerial photographs; creation of shapefiles, elaboration of cartographic products and data interpretation. The results obtained reveal for Nossa Senhora das Dores a landscape derived from the dynamic combination of biophysical and anthropic components. Anthropic interventions are materialized in it, through different types of land use, whose interrelation with the factors of the environmental system results in repercussions on hydrographic dynamics and water resources. The main conditioning factors of the water resources of the study area are: the climate, with two well-defined seasons - dry and rainy, which favors the intermittent river regime; geology - sedimentary and metamorphic lithologies with different degrees of fracturing, associated respectively with granular and fissural aquifers, which have different groundwater storage potentials; geomorphology - topography and altimetry of the model, which interfere with the infiltration and runoff processes; and the historical process of land use and occupation - agricultural activities and the expansion of urban infrastructure, which imply the suppression of vegetation cover and the growing demand for water. In this context, water sources are impacted by deforestation and the disposal of residential effluents. In the analyzed time frame, the growing demand for water, forced the public administration to seek other points of capture for public supply, even outside the political- administrative limits. The water sources where the capture was carried out were replaced by others in which the flow was sufficient to meet consumption, three changes occurred - Quarries, Pedrinhas stream and Sangradouro river. Currently, more than 70% of the population is supplied by water from the Sangradouro river, captured in the Siriri municipality, and the rest of the water consumed comes - from the São Francisco river, through Adutora Sertaneja; tanker cars; tubular wells; the capture of rainwater in cisterns; among others. In view of this reality, it is necessary to plan and manage natural resources and, in particular, water resources in the municipality.